2009
DOI: 10.1002/j.0022-0337.2009.73.3.tb04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Hygiene Students’ Attitudes Toward Ethical Dilemmas in Practice

Abstract: This article reports the findings of a survey-based study conducted in 2006 to determine graduating dental hygiene students' attitudes toward ethical dilemmas in eight areas of practice: substandard care, overtreatment of patients, scope of practice, fraud, confidentiality, impaired professionals, sexual harassment, abuse, and health status. The findings, based on responses from 1,165 students at 141 U.S. dental hygiene programs, indicate that many dental hygiene students do not understand what behaviors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Sexual harassment situations were similar in Brazil and other countries, as reported in previous studies 8 , 16 , 21 , 25 , 27 . The majority of complaints come from women; however the number of complaints filed by men is increasing, along with increasing numbers of men filing against female supervisors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sexual harassment situations were similar in Brazil and other countries, as reported in previous studies 8 , 16 , 21 , 25 , 27 . The majority of complaints come from women; however the number of complaints filed by men is increasing, along with increasing numbers of men filing against female supervisors.…”
Section: Discussionsupporting
confidence: 86%
“…In the dental field, few studies have been published regarding patients and professors and the sexual harassment claims of their students 8 , 12 , 16 , 21 , 25 , 27 . There is some evidence that patients may sexually harass their oral health care providers 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Arendt's notion of ‘action’ helps to differentiate between diploma and baccalaureate degree outcomes as it highlights the importance of action. Action is also supported by the literature in healthcare ethics; decision‐making is not helpful unless it is followed by action . One respondent framed this idea from the perspective of leadership.…”
Section: Resultsmentioning
confidence: 99%
“…Ethical issues reported by fourth‐year dental students at the University of Iowa extramural programme included patients' limited resources, conflicts between professionals, clinical policy or procedures and decisions by patient surrogates . In another study, dental hygiene students were found to be lacking in their understanding of what truly are ethical issues . Whilst students believed strongly that hygienists should report, intervene or teach patients on certain areas like ill‐treatment and sexual harassment, they were less likely to report on matters that can jeopardise their employment.…”
Section: What Are Soft Skills?mentioning
confidence: 99%